Normalisasi Saluran Drainase di Kawasan Pantai Marina Sebagai Upaya Pencegahan Banjir - Radha Purnamasari; Usmanul Hayadi Umar (Faculty of Engineering, Kadiri University, 2022)
Drainage is a basic facility that must be provided to meet community needs, so it’s very important in urban spatial planning. The benefit of building drainage is to prevent stagnant water so that it does not interfere with community activities. The condition of the drainage channels on Jalan Marina isn’t maintained because the dimensions of the channels are small and sedimentation occurs, causing silting of the channels. This causes floods that always occur every year. Re-dimension of the drainage channel was carried out because the initial dimensions could not accommodate the planned flood discharge. Some of data the basic for determining the re-dimensional drainage channels are rainfall data, sea tide data, and initial drainage channel dimension data. From the calculation results, the value of planned flood discharge is 172.634 mᶟ/s. So, the dimensions of the drainage channel are re-planned because the channel discharge value is smaller than the planned flood discharge value. The results of this study are that the planned flood discharge is greater than the drainage channel water discharge so that the initial channel dimensions cannot accommodate water. The results of re-planning the dimensions of the drainage channel based on the planned flood discharge value are h of 8.5 meters, b of 9.8 meters, and W of 2 meters. Re-dimensional planning of the drainage channel is fulfilled because Qs<Qp (172.634 mᶟ/s <227.103 mᶟ/s). This research is expected to provide dimensions of drainage channels that are in accordance with field conditions so that no more flooding occurs.